PROGRAM MANAGEMENT IN NON-FORMAL EDUCATION INSTITUTIONS (CASE STUDY AT AV BIMBEL SAMARINDA): MANAJEMEN PROGRAM PADA LEMBAGA PENYELENGARAAN PENDIDIKAN NON FORMAL (STUDI KASUS DI AV BIMBEL SAMARINDA) - muzfahdhilah; Sri Wahyuni; Wahdatan Nisa; Muhamad Ali Salman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe program management in non-formal educational institutions, with a case study at AV Bimbel Samarinda. This institution is one of the tutoring that serves students from the PAUD to junior high school levels, including children with special needs. This study uses a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation studies, while data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion/verification. The results of the study show that AV Bimbel implements management functions effectively, ranging from planning, implementation, to supervision and evaluation. Planning is carried out in a participatory manner by involving the head of the institution and tutors, and adjusted to the needs of students. The implementation of the program prioritizes fun and personalized learning methods, with a flexible schedule that adjusts to the activities of the participants. Evaluations are carried out periodically through value monitoring and intensive communication between tutors, students, and parents. Factors that support the success of the program include harmonious relationships between institutions, tutors, students, and parents, as well as a conducive learning atmosphere. Meanwhile, the limited number of tutors and supporting facilities is a challenge in itself. Overall, AV Bimbel is able to demonstrate adaptive and student-centered management practices, which can serve as a model for other non-formal educational institutions.